Reconstruction of the Axiological Values of the Ngerateng Lampad Tradition for the Development of a Holistic Character Education Model - I Wayan Sugihartha; I Nyoman Tika; I Wayan Suja (Jurnal Pedagogi dan Pembelajaran, 2026)
Tradition plays an important role in shaping cultural identity and transmitting values; however, globalization and digitalization have encouraged a shift toward individualism and weakened authentic social interactions, contributing to the moral degradation of younger generations. This condition necessitates the reconstruction of character education that is contextual and rooted in local wisdom. This study aims to analyze the axiological values of character education embedded in the Ngerateng Lampad tradition as a reconstruction of local wisdom for contemporary holistic education. The study employed a descriptive qualitative method with an ethnographic approach involving traditional leaders, youth groups, community leaders, and community members who support the tradition. Data were collected through observation, in depth interviews, documentation, and questionnaires, and were analyzed using the Miles and Huberman model, with validity ensured through triangulation and member checking. The findings reveal that the Ngerateng Lampad tradition embodies religious-spiritual values, mutual cooperation, responsibility, environmental awareness, perseverance, discipline, creativity, and wisdom, which are internalized through collaborative, participatory, and holistic ritual processes. The study concludes that the Ngerateng Lampad tradition represents a local wisdom-based pedagogical model capable of fostering holistic character development through meaningful socio-cultural experiences. The findings imply that local cultural values can be systematically integrated into learning processes and curriculum development to strengthen contextual, reflective, and sustainable character education.